Policy response to external shocks: Lessons from the crisis - Carlos Capistrán; Gabriel Cuadra; Manuel Ramos-Francia (Banco de México, 2011)
Emerging economies have been subject to abrupt reversals in capital inflows, which have adverse consequences for economic activity and financial stability. An important question for policymakers is how to respond to a sudden loss of external financing and its negative effects on the domestic economy. The experience of emerging economies through the recent financial crisis shows that those economies with relatively better economic fundamentals were able to implement countercyclical policies. This paper provides a simple analytical framework to rationalize this evidence. In particular, it addresses this issue by developing a small-scale macroeconomic model of the New Keynesian type. Numerical exercises illustrate how both credible monetary and fiscal policies increase policymakers' degrees of freedom to respond to adverse external shocks.
Keywords: E52; E62; F32; F41; 330; reversals in capital flows; emerging economies; monetary policy; fiscal policy; Schock; Kapitalimport; Geldpolitik; Finanzpolitik; Schwellenländer